EXPERIENCE AND OUTCOME OF VENTRICULAR-ATRIAL SHUNT: A MULTI CENTRE STUDY - Akhtar, Nadeem; Khan, Adil Aziz; Yousaf, Muhammad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Ventriculoperitoneal (VP) shunt has been widely utilized in the treatment of hydrocephalus as a safe option but there is recent literature evidence that ventricularatrial (VA) shunt is not as notorious for its complications as proclaimed, to analyse and report our success with this procedure we conducted our study. Methods: A total of 64 patients undergoing VA shunting were included in this case series study conducted at RMC and Allied hospital Rawalpindi. The data was collected over a period of 4 years from, 1st June 2010 to 1st June 2015. Result: Our study included 64 patients who underwent a VA shunt for hydrocephalus. Their age ranged from 25 to 75 years. Most of the patients were females (60%). The following complications were observed with 2 (3.12%) patients having blockage of the shunt at the neck, 3 (4.68%) suffered from glomerulonephritis, 2 (3.1%) had post-operative neck hematoma, 4 (6.25 %) had wound infection, short lower end of the tube was found in 3 (4.68%), migrated lower end (into the subclavian) was seen in 1 (1.56%). Mortality was 1(1.56%). These results were comparable to other studies. Conclusion: Neurosurgeons have been doing a VA shunt as a second procedure, after a VP shunt when the need due to a complication was encountered. We however share our experience regarding ventriculo-atrial shunting, as first choice procedure, because of its low incidence of shunt blockage unlike VP shunt, which has high rate of shunt blockage and therefore warrants repeated surgeries.